Delayed and rapid deglaciation of alpine valleys in the Sawatch Range, southern Rocky Mountains, USA - J. P. Tulenko; W. Caffee; A. D. Schweinsberg; J. P. Briner; E. M. Leonard (Geochronology, 2020)
We quantify retreat rates for three alpine glaciers in the Sawatch Range of the southern Rocky Mountains following the Last Glacial Maximum using 10 Be ages from ice-sculpted, valley-floor bedrock transects and statistical analysis via the BACON program in R. Glacier retreat in the Sawatch Range from at (100 %) or near ( ∼83 %) Last Glacial Maximum extents initiated between 16.0 and 15.6 ka and was complete by 14.2–13.7 ka at rates ranging between 35.6 and 6.8 m a −1 . Deglaciation in the Sawatch Range commenced ∼2 –3 kyr later than the onset of rising global CO 2 and prior to rising temperatures observed in the North Atlantic region at the Heinrich Stadial 1–Bølling transition. However, deglaciation in the Sawatch Range approximately aligns with the timing of Great Basin pluvial lake lowering. Recent data–modeling comparison efforts highlight the influence of the large North American ice sheets on climate in the western United States, and we hypothesize that recession of the North American ice sheets may have influenced the timing and rate of deglaciation in the Sawatch Range. While we cannot definitively argue for exclusively North Atlantic forcing or North American ice sheet forcing, our data demonstrate the importance of regional forcing mechanisms for past climate records.